In Search of a Latin American Approach to Organizational Communication: A Critical Review of Scholarship (2010–2014): En busca de un enfoque latinoamericano de la comunicación organizacional: una revisión crítica de la producción académica de 2010 a 2014 - Vásquez Donoso, Consuelo (2018)
This article presents a critical review of organizational communication scholarship in Latin America to explore its distinctive traits. Combining J. Marques de Melo’s (1999) features of Latin American communication studies with Anglo-American frameworks of organizational communication, it offers a systematic mapping of Latin American organizational communication scholarship by focussing on the major trends of the academic production in peer-reviewed journals from 2010 to 2014. The results show that there are subtle but consistent signs of a Latin American approach to organizational communication regarding theoretical miscegenation and the ethics and political commitment of the researcher. This is mainly manifested in the practical orientation of research and the growing interest in documenting and intervening in local organizational realities.